A new species of the genus Sarcinodes Guenée, [1858] (Lepidoptera, Geometridae) from China - Yu, Tiantian; Wang, Min (Zootaxa, 2020)
The genus Sarcinodes Guenée, [1858]of China is reviewed and totally 9 species are recognized with the description of Sarcinodes hainana sp. nov. from Hainan, China. Sarcinodes lilacina Moore, 1888 is reported for the first time from Yunnan, China. The external morphology of adults, particularly the male and female genitalia, are illustrated. COI sequences were obtained as DNA barcodes for identification of the new species. A key to the Chinese Sarcinodes species is provided.